Energy communities in sustainable transitions - The South American Case - González, Axel Bastián Poque; Viglio, José Eduardo; Ferreira, Lúcia da Costa (Sustainability in Debate, 2022)
Energy communities (ECs) have become an attractive scholarly target in the last years since they promote more sustainable, democratic, and decentralized electrical systems. Thus, a new research line around the alignments established by the European Union (EU) has arisen. Nevertheless, Latin American initiatives and academic works still lack a standard distinctness, being widely spread, despite commonalities. This study examines regional projects from a critical perspective to fashion a novel framework around South American ECs’ experiences. Literature indicates a variety of cases in the region, primarily off-grid isolated ventures that satisfy basic human needs, employing hydropower, solar, wind, biomass, and biogas technologies. Notably, Brazil indicates more profound advancements in on-grid ECs within urban settlements.